Romania : First Review Under the Stand-By Arrangement and Request for Waiver and Modification of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2004)
This paper presents Romania's First Review Under the Stand-By Arrangement and a Request for Waiver and Modification of Performance Criteria. Output growth remains favorable and disinflation is proceeding. The current account deficit is in line with the program's target, and the balance of payments is strengthening. Credit growth in general has slowed, but its foreign currency denominated component has picked up again. Net wage growth remains high, fueling consumption, but labor costs are not deviating substantially from productivity growth.